(untitled) (American Journal of Technology and Applied Sciences, 2025)
Migraine and sleep disorders share complex pathophysiological interactions, influencing each other’s onset and severity. This article explores the peculiarities of migraines in patients suffering from comorbid sleep disorders, emphasizing the impact on clinical presentation, treatment approaches, and quality of life. Through a comprehensive review of existing literature, clinical studies, and data analysis, the study aims to provide insights into the bidirectional relationship between these conditions and propose effective management strategies. A detailed examination of the underlying mechanisms, associated risk factors, and therapeutic approaches is presented to enhance understanding and treatment outcomes.